Perancangan Iklan Layanan Masyarakat Tentang Darurat Kekerasan Seksual - Khaira Syifa (Jurnal Indonesia Sosial Teknologi, 2022)
Public service ads as an object of research aims to provide socialization and disseminate the importance of not blaming the victim's clothes in an incident of sexual violence. The stigma about skimpy outfit is an invitation to sexual violence, which is the basic reason researcher want to explore this topic as research object and the reason this research was made. Sexual violence can happen to anyone, anytime and anywhere. It doesn't matter, if they are skimpy or covered. Even in some cases, their own families can also be victims. This research uses a qualitative method. In the process of preparing this public service ads, researchers anxious to make some media as a means of information facilities public service ads, such as with posters, billboards, totebags, pins, and digital flyers, to make it easier, faster, and kindly for the public to know and see, especially women, as well as parents who always take care of their children from it.